Analisis Efektivitas Metode Kasus dalam Meningkatkan Pemahaman Materi Biaya Overhead Pabrik pada Mahasiswa - Saharsini, Astuning; Sumaryati, Sri; Seto, Bayu (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose –This study investigates the effectiveness of the case method in enhancing students’ conceptual understanding of factory overhead costs in cost accounting courses within the Accounting Education Program at Universitas Sebelas Maret.Method – Adopting a mixed-method sequential explanatory design, the study combined quantitative data from 71 students through questionnaires with qualitative insights from five in-depth interviews. Quantitative data were analyzed using descriptive statistics, while qualitative data were examined thematically to explain the numerical findings. Findings – The findings revealed a substantial improvement in students’ comprehension of cost accounting concepts after participating in case-based learning. The mean understanding score increased from 3.81 to 4.25, indicating a significant enhancement in their ability to differentiate between fixed and variable overhead and to apply cost allocation methods accurately. Reliability analysis produced Cronbach’s Alpha values above 0.85 for all variables, confirming internal consistency. Qualitative data supported the quantitative results, showing that students became more confident in analyzing real-world problems, collaborating in groups, and linking theory to practice. Research Implications – The study demonstrates that the case method can effectively enhance conceptual and applied understanding of cost accounting topics. Practically, it supports the implementation of student-centered and industry-oriented learning strategies to improve graduates’ readiness for professional accounting practice.